2021
DOI: 10.12659/msm.928118
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Effusion Is Associated with Severe Renal Dysfunction in Patients with Acute Pancreatitis

Abstract: Background Renal dysfunction is a leading cause of death in patients with acute pancreatitis (AP) and often occurs later than respiratory complications. Whether respiratory complications can predict renal impairment remains unclear. The aim of this study was to investigate the association between pleural effusion and renal dysfunction in AP. Material/Methods Medical records were reviewed from individuals who were hospitalized with AP from January 1, 2015 to December 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…This study showed that SAP patients with PE rather without PE were more serious and had worse outcome, which was consistent with the previous studies [ 8 , 9 , 23 ]. In addition, this study also drew the same results as before: PE was a risk factor for death, but not an independent risk factor for death of SAP [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study showed that SAP patients with PE rather without PE were more serious and had worse outcome, which was consistent with the previous studies [ 8 , 9 , 23 ]. In addition, this study also drew the same results as before: PE was a risk factor for death, but not an independent risk factor for death of SAP [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recent report suggests that the incidence of PE in AP is up to 50% [ 8 ]. Besides, PE is a good predictor for SAP and even better than Ranson score and Acute Physiology and Chronic Health Evaluation II (APCHE II) score in reflecting the severity of SAP [ 8 , 9 ]. Indwelling pleural catheter (IPC) is effective for benign and malignant PE and could improve living quality of patients by intermittently relieving PE symptoms [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While renal failure is comprehensively addressed in the EuroSCORE system so that an outcome-prediction can be made, frailty itself remains elusive as only age alone is visible as a risk factor. Thus, not only a high BMI can be considered a risk factor, but also an unintentional BMI decline indicating frailty and thus the risk for an adverse outcome [ 23 , 24 ]. Therefore, in addition to the EuroSCORE, an assessment of frailty is needed to make an informed recommendation for surgical or interventional therapy in these patients on an individual basis, especially for demanding procedures with inherent risks such as mitral valve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PE was detected by chest X-ray in eight studies [ 16 , 18 , 20 , 22–24 , 41 , 50 ], by CT in 14 studies [ 19 , 21 , 25–27 , 30 , 32 , 35 , 38 , 39 , 42 , 45–47 ], by transthoracic sonography in one study [ 17 ] and by combination of above methods in four studies [ 29 , 31 , 48 , 49 ]. Other studies did not clearly report the detecting method [ 28 , 33 , 34 , 36 , 37 , 40 , 43 , 44 ]. The general characteristics of the eligible studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%